The measure of civilization how social development decides the fate of nations - Morris, Ian 1960- (Profile Books, 2013)
Offers insight into the index of social development that measures change in East and West. The author argues that to understand the development of East and West, we need to look beyond 'long-term lock-in' theories (that suggest it was inevitable) and 'short-term accident' theories.